Oral lesions in kidney transplant recipients - Katarina Levarda-Hudolin; Tvrtko Hudolin; Nikolina Bašić-Jukić; Željko Kaštelan (Acta Clinica Croatica, 2016)
Permanent immunosuppression is necessary to prevent rejection after kidney transplantation. However, it may predispose patients to different conditions and diseases including oral lesions. The most common benign oral lesions in kidney transplant recipients are gingival hyperplasia, oral candidiasis, hairy leukoplakia and saburral tongue. Oral form of Kaposi sarcoma, although rarely, can also be seen in kidney transplant patients. In this review, we present the incidence, etiology, clinical findings, diagnosis and treatment options for these lesions. For kidney transplant recipients, it is important to maintain good oral hygiene and care, as well as regular professional control by the dentist. This approach can reduce the number and severity of oral lesions.